Epidemiological assessment of the prevalence of coxarthrosis according to reports from medical organizations - V. A. Koryak; A. D. Botvinkin; V. A. Sorokovikov (Acta Biomedica Scientifica, 2022)
Background. Coxarthrosis prevalence rates are necessary to assess the socio-economic significance of this pathology and to calculate the need for endoprosthetics. Information about the provision of medical care to patients with coxarthrosis is presented in the reports of various medical organizations, but in state statistical reports at the regional level this nosological form is not taken into account as a separate line.The aim. To estimate the prevalence of coxarthrosis based on the combined use of medical records from various sources in a region with a specialized clinic for prosthetics of large joints.Materials and methods. A retrospective descriptive epidemiological study based on materials from the Irkutsk region for 10 years (2008–2017) was carried out. Three main sources of data on patients with coxarthrosis were used: continuous and randomized samples based on population visits to polyclinics (n = 24 029), information from the bureau of medical and social expertise on disability (n = 19 081) and information from a specialized clinic on total hip arthroplasty (THAP) (n = 6227). The dynamics of indicators by years, the distribution of patients by sex, age and groups of disabilities have been analyzed. Regional indicators of incidence and prevalence of coxarthrosis were calculated based on extrapolation of sample data.Results. The following average annual regional indicators for patients with coxarthrosis were calculated: primary visits to polyclinics (incidence) – 73.8 (71.9–75.7) with a frequency of visits 1.9 times a year, the frequency of THAP operations – 3,3 (3,0÷3,6), disability – 10.1 (10.0÷10.3). The median age of patients at the initial visit was 61 years (Q1 = 46; Q3 = 76). The proportion of men among different groups of patients ranged from 41 to 44%, the proportion of disabled people among patients of the polyclinic and surgical hospital – from 45.2 to 47.1%. The estimated prevalence of coxarthrosis among the adult population was 413.5 (410,6÷416,4) / 10000.Conclusions. The epidemiological analysis algorithm described in the article is proposed as the first stage in assessing the social and economic significance of coxarthrosis and the regional need for arthroplasty of large joints.